Islam Nusantara: Strategi Perjuangan â€œKeumatanâ€ Nahdlatul Ulama - Ahmad Khoirul Mustamir (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
The Islamic Discourse of the Archipelago increasingly found its momentum in the struggle for the meaning of Islam. Many are pros and not a few cons. The pros, driven by the NU religious movement. While those who are cons, radical groups are identified. In this context, it is important to study more deeply about Islam Nusantara. This research uses the method of library research or Library Research. A literature study is a data collection technique by conducting a study of books, literature, notes, and reports that are related to the problem being solved. This article utilizes journals, materials and relevant information to be collected, read and reviewed, recorded as a guide or reference source. The results showed that the ability of Islamic da'wah to adapt to local culture made it easier for Islamic da'wah to enter the lowest strata of society. Inevitably, Islam as a religion that spreads throughout the world appears creatively in dialogue with the local community (local), is in a position to accept the traditions of the community, while modifying it into a new culture that can be accepted by the local community and still within the path of Islam. Therefore, the arrival of Islamic da'wah is enlightenment for the Southeast Asian region, especially Indonesia.